Antibacterial Activity of Zanthoxylum chalybeum, Aloe deserti, and Zanthoxylum usambarense. - Maithulia, Stephen Mugambi; Chumba, Careen Ihazano; Maingi, John Muthini; Mburu, David Ng'ang'a; Njagi, Eliud Nyaga Mwaniki; Gurumallesh Prabu, Poorani (BioMed Research International, 2026)
Various Gram‐positive and Gram‐negative enteric pathogens are responsible for bacterial gastroenteritis, and this condition is commonly treated with antibiotics. But, the growing prevalence of antimicrobial resistance and drug‐associated toxicities has diminished the effectiveness of conventional drugs, prompting the need for alternative remedies, especially from medicinal plants. This study assessed the in vitro antibacterial potential of Zanthoxylum chalybeum and Zanthoxylum usambarense and Aloe deserti. Standard bacterial strains from the Kenya Medical Research Institute were employed for antibacterial assays. Antibacterial activities were determined by means of inhibition zone diameters, MICs, MBCs, and time‐kill kinetics. Methanol extracts from Zanthoxylum chalybeum and Aloe deserti had no antibacterial activity. In contrast, the methanolic extract of Zanthxylum usambarense exhibited antibacterial action in a concentration‐ and time‐dependent fashion, with very potent efficacy against Bacillus cereus, Bacillus subtilis, and Staphylococcus aureus, moderate against Enterococcus faecalis, and low against Escherichia coli. Time‐kill studies confirmed rapid bactericidal action against susceptible Gram‐positive bacteria. Phytochemicals detected include alkaloids, flavonoids, tannins, terpenoids, and glycosides, as well as trace and heavy metals. Zanthoxylum usambarense exhibited remarkable antibacterial effect against Gram‐positive bacteria, but limited activity was exhibited against Gram‐negative strains. However, the present study was limited to in vitro testing, and post‐extraction quality control testing was not included. Thus, clinical application of the results cannot be made. Further studies are needed to identify the active constituents of the extract, toxicity, efficacy, and standardization of the extract.